2019
DOI: 10.1111/ajt.15223
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin in posttransplantation diabetes mellitus: A prospective, interventional pilot study on glucose metabolism, fluid volume, and patient safety

Abstract: The safety and efficacy of sodium‐glucose cotransporter 2 inhibitors in posttransplantation diabetes mellitus is unknown. We converted stable kidney transplant patients to 10 mg empagliflozin, aiming at replacing their insulin therapy (<40 IU/d). N = 14 participants (the required sample size) completed the study visits through 4 weeks and N = 8 through 12 months. Oral glucose tolerance test (OGTT)–derived 2‐hour glucose (primary end point) increased from 232 ± 82 mg/dL (baseline) to 273 ± 116 mg/dL (4 weeks, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
143
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(193 citation statements)
references
References 30 publications
14
143
1
2
Order By: Relevance
“…Extracellular water was reduced rapidly and significantly after 3 days, but had returned to baseline value when measured after three and 6 months. In a cohort of post-transplant diabetes mellitus, Schwaiger et al[11] also found a decrease of extracellular fluid after 4 weeks and extracellular water returned to baseline value in the further course. In Japanese patients treated with ipragliflozin, Iizuka et al[8] found a reduction of total body water by − 0.43 kg at 4 weeks, and a rising tendency at 12 weeks (− 0.37 kg), compared to baseline, respectively, with changes of body fluid mainly caused by extracellular water and no significant changes of intracellular water; however, changes of volume status during the first days Friedman-Test: Χ² (10) = 5.182 p = 0*p < 0.008 (significant with Bonferroni correcƟon); #p < 0.05 Course of serum aldosterone concentration (a) and plasma renin activity (b) under treatment with SGLT2 inhibitors.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Extracellular water was reduced rapidly and significantly after 3 days, but had returned to baseline value when measured after three and 6 months. In a cohort of post-transplant diabetes mellitus, Schwaiger et al[11] also found a decrease of extracellular fluid after 4 weeks and extracellular water returned to baseline value in the further course. In Japanese patients treated with ipragliflozin, Iizuka et al[8] found a reduction of total body water by − 0.43 kg at 4 weeks, and a rising tendency at 12 weeks (− 0.37 kg), compared to baseline, respectively, with changes of body fluid mainly caused by extracellular water and no significant changes of intracellular water; however, changes of volume status during the first days Friedman-Test: Χ² (10) = 5.182 p = 0*p < 0.008 (significant with Bonferroni correcƟon); #p < 0.05 Course of serum aldosterone concentration (a) and plasma renin activity (b) under treatment with SGLT2 inhibitors.…”
mentioning
confidence: 89%
“…Previous investigations of changes in body composition under SGLT2 inhibitors mainly relied on calculated indices or x-ray absorptiometry [5][6][7]. In contrast, quantitative measurements of body composition have only lately been performed in a few cohorts [8][9][10][11]. Early changes of body composition during the first days after initiation of SGTL2 inhibitors have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the rationale that novel antidiabetic agents have been shown to be immensely beneficial in the general population with T2DM, the SGLT2i empagliflozin was used at the Vienna transplant center in patients with PTDM after kidney transplantation, in a study which resulted in the formally first publication on this subject (the EMpagliflozin in Post‐TRAnsplant Diabetes Mellitus [EMPTRA‐DM] pilot study [111]). Only a few months later, the transplant center in Oslo also published a randomized controlled study on empagliflozin administration after kidney transplantation (EMPA‐Renal Tx [112]), and several other studies have followed on kidney [113‐115] and heart [116,117] transplant patients.…”
Section: Management Of Ptdm: Novel Antidiabeticsmentioning
confidence: 99%
“…In both cases, renal function did not decrease and UACR decreased after administration of empagliflozin. Regarding the decrease in UACR, it is possible that the improvement of tubuloglomerular feedback associated with natriuresis by empagliflozin was involved in the case of also CKD stage3a [15,20,22,25]. The decrease in UACR in both cases may lead to renal protection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, studies have addressed the issue of SGLT2 inhibitor administration to renal transplant patients [14]. For example, Schwaiger et al [15] assessed the impact of replacing insulin with empagliflozin 10 mg/day in 14 stable kidney transplantation patients with diabetes mellitus. Although the administration of empagliflozin alone decreased glucose and HbA1c levels, the patients lost an average of 1.6 kg over 4 weeks.…”
Section: Discussionmentioning
confidence: 99%